Significances of blowing and suction processes on the occurrence of thermo-magneto-convection phenomenon in a narrow nanofluidic medium: A revised Buongiorno's nanofluid model - Zaydan, M.; Wakif, A.; Animasaun, I.L.; Khan, Umair; Baleanu, Dumitru; Sehaqui, R. (Case studies in thermal engineering, 2020)
In this numerical examination, the thermal stability of an electrically conducting nanofluid is deliberated comprehensively by considering the presence of an externally applied magnetic field along with an imposed vertical throughflow. Additionally, this thin nanofluidic layer is supposed to have a Newtonian rheological behavior, heated from below, and confined horizontally between two permeable rigid plates of infinite extension. Herein, the governing conservation equations are strengthened realistically by the revised version of the Buongiorno's mathematical model, in which the vertical component of the mass flux of solid nanoparticles is presumed to vanish entirely at the horizontal permeable boundaries. After specifying the basic state of the present nanofluid problem, the linear stability theory and normal mode analysis technique are applied properly to obtain the principal stability equations. Finally, the eigenvalue problem derived analytically is tackled thereafter numerically via the Chebyshev-Gauss-Lobatto Spectral Method (CGLSM), in which the thermal Rayleigh number is chosen as an eigenvalue. As a main result, it was demonstrated that the throughflow effect exhibits a dual behavior on the complex dynamics of the system. However, the excreted magnetic field has always a stabilizing impact on the nanofluidic medium.